Environmental Legal Protection Against Mangrove Forest Destruction In Lantebung Area, Makassar City - Hasriani Hamid; Muhammad Said Karim; Maskun Maskun (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
This study aims to examine the position of environmental permits in the perspective of environmental crimes against cases of mangrove forest destruction in Makassar City. This study uses a normative-empirical research method, namely the type of normative legal research that is supported and equipped with empirical data. The research approach method used is the statutory approach and the case approach. The types and sources of data used are primary data and secondary data. Furthermore, both secondary and primary data were analyzed using qualitative analysis techniques and presented descriptively. The results of this research are: The position of environmental permits in the perspective of environmental crimes is an absolute thing to be fulfilled. The environmental permit which was originally regulated in UUPPLH has now been amended in a new regulatory provision, namely Article Number 11 of 2020 concerning Job Creation is an environmental agreement. The nomenclature is different, but the meaning remains the same, namely both environmental permits and environmental approvals are needed to limit the space for business actors to move so as not to deviate from the permits given.